Diretrizes para a educação ambiental em cursos técnicos - Coleto, Aline Cristina (2012)
The pedagogic proposal, based on the interdisciplinarity and constant relation between theory and practice, favors the implementation of the environmental education in the technical courses. However, the studies about environmental education devoted straightly to this kind of teaching are still scarce. The aim of the present dissertation consists in proposing directives for the practice of the environmental education in technical courses, identifying the conception of students and teachers about environment and environmental education, besides demonstrating the importance of the environmental education and his interfaces in technical courses. The present dissertation is based on a qualitative and quantitative descriptive, bibliographical and documentary research method. Questionnaires were applied to students and teachers of technical courses. The answers were categorized and analyzed to diagnose how the environmental education is teaching in this kind of course. The results showed that the importance of the environmental education in technical courses is recognized by the students and teachers, but the actions are not integrated. Most of the teachers do not know the curricular parameters national and they have difficulties in boarding the environmental questions through the interdisciplinarity and cross subject. Finally, based on the comparison between the refined results and the legal determinations for the environmental education in technical courses, are suggested education and management directives for the effectiveness of the environmental education that contemplate the specific necessities of this kind of teaching.